Unilateral versus bilateral cerebral perfusion during aortic surgery for acute type A aortic dissection: a multicentre study. (23rd July 2021) - Piperata, Antonio; Watanabe, Masazumi; Pernot, Mathieu; Metras, Alexandre; Kalscheuer, Gregory; Avesani, Martina; Barandon, Laurent; Peltan, Julien; Lorenzoni, Giulia; Jorgji, Vjola; Gregori, Dario; Takahashi, Shinya; et al.
Abstract: OBJECTIVES: The aim of this retrospective multicentre study was to investigate and compare clinical outcomes of unilateral and bilateral antegrade cerebral perfusion (ACP) strategies on cerebral protection during surgery for type A aortic dissection. METHODS: Data from 646 patients who underwent surgical repair of thoracic type A aortic dissection using unilateral and bilateral ACP with moderate hypothermic circulatory arrest in 3 cardiac surgical institutions between 2008 and 2018 were analysed. Propensity matching was performed to assess which technique ensured better outcomes. RESULTS: Unilateral and bilateral ACP techniques were performed in 250 (39%) and in 396 (61%) patients, respectively. Propensity score analysis identified 189 matched pairs. In the matched cohort, the lowest core temperature was 27.5°C and 28°C in the bilateral and unilateral groups, respectively ( P  < 0.001). The unilateral technique required significantly shorter aortic cross-clamp and cardiopulmonary bypass times than bilateral technique [82 min vs 100 min ( P  < 0.001); 170 min vs 195 min ( P  < 0.001)]. The 30-day mortality was comparable ( P  = 0.325). The bilateral group reported a significantly higher incidence of permanent neurologic deficits ( P  < 0.001), left brain hemisphere stroke ( P  = 0.007) and all-combined complications ( P  < 0.001). Ten-year survival was comparable ( P  = 0.45). CONCLUSIONS: Unilateral and bilateral ACP are both valid brain protection strategies in the landscape of aortic arch surgery. While admitting all the study limitations, unilateral technique could offer some clinical advantages. Clinical registration number: 76049 Abstract : The surgical treatment of acute type A aortic dissection (ATAAD) remains one of the biggest technical challenges in cardiac surgery.